Food quality score and anthropometric status among 6‐year‐old children: A cross‐sectional study. Issue 6 (11th March 2021) - Askari, Mohammadreza; Daneshzad, Elnaz; Bellissimo, Nick; Suitor, Katherine; Dorosty‐motlagh, Ahmad Reza; Azadbakht, Leila
Abstract: Objective: Weight status and growth during childhood are indicative of healthy development throughout the lifespan. It is well understood that dietary patterns and overall quality of diet can prevent disease, improve health status and optimise growth and development. The current study investigates the relationship between overall diet quality and measures of childhood development including body mass index and height‐for‐age in 6‐year‐old children. Methods: This cross‐sectional study was conducted across 788 6‐year‐old children from Tehran, Iran, in 2018. Food quality score (FQS) was used to assess overall diet quality, in addition to a modified food‐based diet quality score specific to children (modified FQS) developed by our group. Results: Participants in the highest tertile using the modified FQS had the highest height‐for‐age z‐score (HAZ) (−0.509 ± 0.028 vs −0.605 ± 0.028; P  = .048). In contrast, participants in the highest tertile assessed using the original FQS had a higher BMI for age z‐score (BAZ) compared to participants in the first tertile (0.391 ± 0.072 vs 0.266 ± 0.072; P  = .023). Children within the highest tertile, according to the original FQS, compared to those within the lowest tertile were 49% less likely to be categorised as severely underweight (OR: 0.51; 95% CI: 0.47‐0.98). Conclusions: Findings presented in this study demonstrate that FQS was significantly associated with participants characterised as severely underweight; however, FQS was not associated with other anthropometric parameters. Therefore, future well‐designed cohort studies are required to address limitations of the current study.